Prevalence, risk factors and psychosocial status of obese and overweight adolescents in Hebron city, Palestine - Badrasawi, Manal.; Abu.Snouber, Laith.; Al-Tamimi, Mohammed A; Badrasawi, Kamal J I (Wolters Kluwer, 2019)
Background and aims: Obesity and overweight among children and adolescents have caused a prime public health apprehension because they are significantly associated with medical and psychosocial comorbidity. Children with high body mass index often become obese adults, who are at risk of many chronic conditions such as diabetes and cardiovascular disease. It is vital to further examine obesity and overweight in school children and identify their modifiable risk factors. Therefore, this cross-sectional study aims to explore the prevalence of obesity and overweight among Palestinian adolescents in secondary schools, and their relationship with sociodemographic factors, dietary habits, lifestyle, and healthy nutrition awareness. Methods: The participants were randomly selected from four different areas in Hebron city, Palestine. A total sample comprising 392 students, females (51.3%) and males (48.7%), was included in the final analysis. The nutritional status was assessed using anthropometric measurements and dietary habits. Obesity and overweight were defined using World Health Organization–Centers for Disease Control and Prevention sex-specific growth chart for children, aged 2 to 18 years. Anxiety, stress, and depression were assessed using Arabic version of the Depression Anxiety Stress Scales. Results: The results revealed that obesity prevalence was 3.3% and overweight was 13.8% among the students, with no significant association with gender, age, or area of living. Obesity and overweight were significantly associated with lower self-satisfaction (P<0.01). Conclusion: Considerable prevalence levels of obesity and overweight were reported among the study sample. There is a need to promote intervention educational programs to increase students’ awareness on obesity and overweight, and promote healthy diet intake and lifestyle among them.